Private Tuition and Its Implications on Quality Secondary Education - Snehi, Neeru (JOURNAL OF INDIAN EDUCATION, 2010)
Provision of quality school education is one of the major challenges before the Government in the present times. Reforms initiated in school education sector are aiming at expansion and creation of an effective and high quality educational environment for all children. At the same time emerging education scenario is highly competitive and market oriented. Phenomenon of private tuitions has gained firm footing for enhancing one’s performance in school, public examinations and admission or entrance competitions. Over the years, it has grown from an individual paid job to a professional institutionalised system. Nevertheless, the practice of private tuitions has affected the quality of education system in general and particularly secondary education system in India. The paper attempts to bring forth the factors influencing the growth of private tuitions and their implication on quality of teachers, teaching-learning process, classroom/school environment and other related dimensions.